Inflammation, Nitro-Oxidative Stress, Impaired Autophagy, and Insulin Resistance as a Mechanistic Convergence Between Arterial Stiffness and Alzheimer’s Disease - Hendrickx, Jhana O.; Martinet, Wim; Van Dam, Debby; De Meyer, Guido R. Y. (Frontiers in Molecular Biosciences, 2021)
The average age of the world’s elderly population is steadily increasing. This unprecedented rise in the aged world population will increase the prevalence of age-related disorders such as cardiovascular disease and neurodegeneration. In recent years, there has been an increased interest in the potential interplay between cardiovascular diseases and neurodegenerative syndromes, as several vascular risk factors have been associated with Alzheimer’s disease. Along these lines, arterial stiffness is an independent risk factor for both cardiovascular and Alzheimer’s disease. In this review, we discuss several inflammaging-related disease mechanisms including acute tissue-specific inflammation, nitro-oxidative stress, impaired autophagy and insulin resistance which may contribute to the proposed synergism between arterial stiffness and Alzheimer’s disease.